Simulation of propane-air premixed combustion process in randomly packed beds. (August 2018) - Jiang, Linsong; Liu, Hongsheng; Suo, Shaoyi; Xie, Maozao; Bai, Minli
Highlights: A method is proposed to build real geometric structures of packed beds of particles. Propane-air premixed combustion process in randomly packed beds is simulated. Research flame characteristics during combustion process under different condition. Flame fractal dimension is calculated at different instants under different condition. Flame regimes under different condition are identified. Abstract: Real geometric structures of randomly packed beds are modeled using the discrete element software LIGGGHTS. The wall-adapting local eddy-viscosity (WALE) model and the EBU-Arrhenius combustion model are used to simulate the propane-air premixed combustion process in the randomly packed beds, and the calculated results are compared with experimental data. The results reveal that the turbulence model and combustion model used in this paper are reasonable. Next, propagation velocity, area, mean vorticity and fractal dimension of a flame surface are calculated at various time points with different inlet velocities to investigate the changes in flame characteristics during the combustion process and the effect of increasing the inlet velocity. According to our results, the flame propagation velocity changes do not exhibit a clear trend over time. However, the variation trends of the two curves under the different inlet velocities are similar. In addition, the fractal dimension exhibits no obvious rule of increasing or decreasing during the combustion process. The area and mean vorticity of the flame surface increase with time. However, the rules of increase are not exactly the same. In addition, the flame regimes at various time points are identified. The results reveal that the turbulent premixed flames in a packed bed under two inlet velocities are concentrated in the thin reaction zone.